Systematising career progression : advanced and continuing training in the electrical sector - Müller, Karlheinz [Verfasser]; Schenk, Harald [Verfasser] (My University, 2011)
"To tailor the development of skilled workers to the industry's needs, as of August 2009 a processoriented system of continuing vocational education and training (CVET) has been instituted in the German electrical and electronics sector: having completed initial vocational education and training (IVET) in an electrical and electronics training occupation, skilled workers can pursue further CVET to qualify as Specialists and then gain a second-stage recognised qualification as a Certified Process Manager in Electrics/Electronics (Operative Professional). The realisation of a third-stage advanced training qualification (Strategic Professional) is planned for 2012. This article outlines the innovative structure and the standards governing the content of this new advanced training model. It focuses on the potential of this form of CVET, which is work-process-oriented, undertaken in tandem with work to keep pace with constant advances in technology and organisation." (Autorenreferat, BIBB-Doku)
Keywords: S 1.5 Weiterbildung; G 2.4.1 Bildungs- und Berufswege; S 6.2.4 Elektroberufe; Elektrotechnik; Berufliche Weiterbildung; Aufstiegsfortbildung; Arbeitsprozessorientierung; Qualifikationsprofil